Pengaruh Media Visual dan Motivasi Belajar Terhadap Prestasi Belajar pada Pelajaran Ekonomi Siswa Kelas XII IPS SMA Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Ellyster Marpaung; Binur Panjaitan; Liyus Waruwu (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
In the digital era and information technology, visual media, such as images, videos and animations, have become an integral part of the learning process. Learning motivation is also an important factor in determining the extent to which students are involved in learning. This research focuses on the lack of use of visual media in learning, obstacles to school infrastructure, low student learning achievement, lack of student motivation to learn, and the lack of variety in visual media used by teachers. This research aims to analyze the influence of the use of visual media and learning motivation on achievement studying economics for class XII students at SMA Negeri 1 Sipoholon, North Tapanuli Regency for the 2023/2024 academic year. The research method used is quantitative descriptive. The population was 100 students from class The results of data analysis show that 1) There is a positive and significant influence of Visual learning media on the economic learning achievement of class XII IPS students at SMA Negeri 1 Sipoholon for the 2023/2024 academic year. XII IPS SMA Negeri 1 Sipoholon Academic Year 2023/2024 3) There is a positive and significant influence of visual media learning and learning motivation on economic achievement in class XII class XII IPS SMA Negeri 1 Sipoholon Year 2023/2024. 1) hypothesis testing obtained a coefficient of determination of 51.98% and Fcount>Ftable, namely 11.724>2.06, thus it is known that there is a positive influence of variable X1 with variable Y, 2) hypothesis testing obtained a coefficient of determination of 77.616% and Fcount>Ftable, namely 103.057>2.06. Thus it is known that there is a positive influence of variable together with variable Y. Thus Ha is accepted and Ho is rejected.